2017
DOI: 10.1097/md.0000000000005972
|View full text |Cite
|
Sign up to set email alerts
|

Weight-based contrast administration in the computerized tomography evaluation of acute pulmonary embolism

Abstract: Compare individualized contrast protocol, or weight-based protocol, to standard methodology in evaluating acute pulmonary embolism.Retrospective chart review was performed on patients undergoing computed tomography angiography with standard contrast protocol (n = 50) or individualized protocol (n = 50). Computerized tomography images were assessed for vascular enhancement and image quality.Demographics were comparable, however, more patients in the individualized group were admitted to intensive care unit (48%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…For smaller patients, a lower dose of contrast can be used, with a study by Chen et al showing no statistical difference in the degree of opacification in the PA when using a 60 mL volume of contrast in comparison to 75 mL [27]. Typical contrast dosing between 60 mL and 150 mL have been quoted previously in the literature [28]. Therefore, weight-based contrast dosing can allow for a lower dose of contrast to be used without affecting CTPA study quality, thereby decreasing dose-dependent adverse reactions including acute kidney injury and overall financial cost of contrast use [29].…”
Section: Discussionmentioning
confidence: 99%
“…For smaller patients, a lower dose of contrast can be used, with a study by Chen et al showing no statistical difference in the degree of opacification in the PA when using a 60 mL volume of contrast in comparison to 75 mL [27]. Typical contrast dosing between 60 mL and 150 mL have been quoted previously in the literature [28]. Therefore, weight-based contrast dosing can allow for a lower dose of contrast to be used without affecting CTPA study quality, thereby decreasing dose-dependent adverse reactions including acute kidney injury and overall financial cost of contrast use [29].…”
Section: Discussionmentioning
confidence: 99%
“…Frush et al demonstrated that FV CM protocol yielded better contrast enhancement even though this method scored lower grade in qualitative assessment [21]. Regardless of the technique used, in achieving comparable vascular enhancement and satisfactory image quality, Laurent et al suggested that CM administration protocol should be individualised according to patient habitus [22].…”
Section: Discussionmentioning
confidence: 99%
“…A primary determinant of vascular enhancement is the bolus volume, concentration, and rate of IV contrast media supplied prior to or during the CT acquisition. Many institutions use a fixed volume of contrast media for abdominal scans, but a growing number of studies suggest weight-based protocols offer more consistent image quality across a range of body weights, and at lower total contrast usage and cost [23][24][25][26]. Nevertheless, average blood volumes in women are lower than those in men for a given body size, and results presented here are consistent with past studies finding higher female aorta enhancement (291 ± 49 HU vs. 260 ± 55 HU) that was not accounted for by weight [27][28][29].…”
Section: Plos Onementioning
confidence: 99%